1998
DOI: 10.1007/s004380050694
|View full text |Cite
|
Sign up to set email alerts
|

Tdd-3, a tRNA gene-associated poly(A) retrotransposon from Dictyostelium discoideum

Abstract: The full-length 5218-bp sequence of the mobile genetic element Tdd-3 from Dictyostelium discoideum is described. Tdd-3 encodes two overlapping open reading frames (ORFs) flanked by non-redundant, untranslated regions. The deduced amino acid sequence of ORF2 is homologous to reverse transcriptases (RTs) encoded by the class of poly(A) retrotransposons. ORF2 also encodes a putative protein domain related to the family of apurinic/apyrimidinic (AP) endonucleases, whose retroelement-encoded homologs have recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…This suggested that both elements evolved from a common ancestor capable of inserting downstream of tRNA genes. In a more recent study [65] the full-length 5.2-kb DNA sequence of Tdd-3 was obtained. Tdd-3 elements encode two overlapping ORFs flanked by nonredundant UTRs.…”
Section: Tdd-3 and Red Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggested that both elements evolved from a common ancestor capable of inserting downstream of tRNA genes. In a more recent study [65] the full-length 5.2-kb DNA sequence of Tdd-3 was obtained. Tdd-3 elements encode two overlapping ORFs flanked by nonredundant UTRs.…”
Section: Tdd-3 and Red Elementsmentioning
confidence: 99%
“…3). Tdd-3 elements appear to be transcribed into full-length RNAs during vegetative growth of D. discoideum [65], a prerequisite for transposition. The promoter regulating the transcription of Tdd-3 RNAs is located within the first 360 bp at the 5% end of the Tdd-3 element (T.W., unpublished results).…”
Section: Tdd-3 and Red Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…50 bp upstream of tRNA genes (Table 1). TRE3-A was the first non-LTR retrotransposon found to insert specifically downstream of D. discoideum tRNA genes (Winckler et al, 1998). The Dictyostelium genome project discovered three more TRE3-A-related elements, named TRE3-B, TRE3-C, and TRE3-D (Table 1; Glöckner et al, 2001).…”
Section: Discoideum Non-ltr Retrotransposonsmentioning
confidence: 99%